Developmental brain anomaly due to fetal hydrocephalus - Das, Suman; Chattejee, Kaushani; Mazumdar, Jayitri; Sarkar, Nirmalya; Aich, Bholanath (Journal of Pediatric Neuroradiology, 2013)
In this article, the authors intend to illustrate a striking brain malformation due to early onset severe fetal hydrocephalus that superficially suggests the presence of semilobar holoprosencephaly.
Keywords: Developmental brain anomaly; fetal hydrocephalus; semilobar holoprosencephaly